BS EN ISO 10893-10 AMD1. Non-destructive testing of steel tubes. Part 10. Automated full peripheral ultrasonic testing of seamless and welded (except submerged arc-welded) steel tubes for the detection of longitudinal and/or transverse imperfections (2nd September 2019) - British Standards Institution,
No abstract available